Effect of the number of unhealthy lifestyles in middle-aged and elderly people on hypertension and the first occurrence of ischemic stroke after the disease - Zhu, Xiaopeng; Zhang, Fang; Luo, Zhongyan; Liu, He; Lai, Xia; Hu, Xiaotong; Xie, Qian; Gao, Xia; Long, Yan (Frontiers in Cardiovascular Medicine, 2023)
To determine the relationship between the number of controllable unhealthy lifestyles on the risk of hypertension and the first occurrence of ischemic stroke after the disease in elderly people in the community, and to provide data support and basis for community physicians to guide hypertensive patients to control modifiable risk factors to prevent the first occurrence of ischemic stroke.